Ergogenic effect of acute supplementation guarana in jiu-jitsu fighters - Silveira, Jacqueline Queiroz da [UNESP]; Amorim, Leidiane Lara; Burian, Joao Paulo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Caffeine is a widely studied ergogenic supplement, however, studies that associate caffeine present in guarana with application in adolescents are scarce. Thus, the objective of this research was to evaluate the ergogenic effects of acute encapsulated guarana powder supplementation on adolescent jiu-jitsu fighters. For the lactate test and the subjective perception of the effort, the fighters simulated the Morote Gari for two minutes at maximum intensity, after 60 minutes of supplementation. An anthropometric evaluation, blood pressure measurement, lactacidemia and application of the Borg scale were performed. The experiment consisted of a blind procedure for three consecutive days: 1) without supplementation, 2) placebo and 3) with supplementation, with the participation of six adolescent fighters. In the evaluation of nutritional status, all athletes presented eutrophic. As for the physiological tests, the increase in lactacidemia and the number of blows after guarana supplementation are highlighted. This result suggests that athletes have become more tolerant to exercise after supplement intake, indicating that guarana powder can be used as an ergogenic resource to improve the performance of jiu-jitsu fighters.
Keywords: Guarana; Caffeine; Jiu-jitsu